Question

(D) The sum of the first three terms of an arithmetic sequence is 36 and their product is 1140. Determine the three terms.

Ask by Summers Edwards. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The three terms are 5, 12, and 19.

Solution

Let's find the three terms of the arithmetic sequence step by step. ### Step 1: Represent the Terms Let the three terms be: \[ a - d, \quad a, \quad a + d \] where \( a \) is the middle term and \( d \) is the common difference. ### Step 2: Sum of the Terms The sum of the first three terms is given as 36: \[ (a - d) + a + (a + d) = 3a = 36 \implies a = 12 \] ### Step 3: Product of the Terms The product of the three terms is given as 1140: \[ (a - d) \cdot a \cdot (a + d) = a(a^2 - d^2) = 1140 \] Substituting \( a = 12 \): \[ 12(144 - d^2) = 1140 \implies 144 - d^2 = 95 \implies d^2 = 49 \implies d = 7 \quad (\text{since } d \text{ is positive}) \] ### Step 4: Determine the Terms Now, substitute \( a = 12 \) and \( d = 7 \): \[ a - d = 12 - 7 = 5 \] \[ a = 12 \] \[ a + d = 12 + 7 = 19 \] ### Verification - **Sum:** \( 5 + 12 + 19 = 36 \) - **Product:** \( 5 \times 12 \times 19 = 1140 \) Both conditions are satisfied. **Answer:** The three terms are 5, 12, and 19.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

Let the first term of the arithmetic sequence be \( a \), and the common difference be \( d \). Therefore, the first three terms can be expressed as \( a \), \( a + d \), and \( a + 2d \). According to the problem: 1. The sum of the three terms is given by: \[ a + (a + d) + (a + 2d) = 3a + 3d = 36 \] This simplifies to: \[ a + d = 12 \quad (1) \] 2. The product of the three terms is given by: \[ a(a + d)(a + 2d) = 1140 \] Substituting \( d = 12 - a \) from equation (1) into the product gives us: \[ a(a + (12 - a))(a + 2(12 - a)) = 1140 \] Simplifying this: \[ a(12)(24 - a) = 1140 \] This expands to: \[ 12a(24 - a) = 1140 \] Dividing both sides by 12: \[ a(24 - a) = 95 \] This leads to the quadratic equation: \[ a^2 - 24a + 95 = 0 \] 3. To find \( a \), we can use the quadratic formula: \[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{24 \pm \sqrt{576 - 380}}{2} = \frac{24 \pm \sqrt{196}}{2} = \frac{24 \pm 14}{2} \] This yields two potential solutions for \( a \): \[ a = \frac{38}{2} = 19 \quad \text{or} \quad a = \frac{10}{2} = 5 \] 4. Now we can find \( d \) for both values: - If \( a = 19 \): \[ d = 12 - 19 = -7 \] The terms would then be \( 19, 12, 5 \). - If \( a = 5 \): \[ d = 12 - 5 = 7 \] The terms would then be \( 5, 12, 19 \). Thus, the three terms of the arithmetic sequence are \( 5, 12, 19 \).

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy